Broadband and Fabrication Tolerant Power Coupling and Mode‐Order Conversion Using Thouless Pumping Mechanism. Issue 11 (7th August 2022) - Sun, Lu; Wang, Hongwei; He, Yu; Zhang, Yong; Tang, Guojing; He, Xintao; Dong, Jianwen; Su, Yikai
Abstract: Coupled‐waveguide devices are of central importance in on‐chip photonic circuits. However, their performance usually suffers from high wavelength and structure sensitivity, which makes it challenging to achieve broadband and fabrication tolerant optical functions. Topological pumping of edge states has emerged as a promising route for robust light transport in coupled waveguides. Here, the Thouless pumping process is explored in finite Rice‐Mele modeled silicon waveguide arrays and the robust power coupling and mode‐order conversion are experimentally demonstrated in this system. Thanks to the topological protection of light transport, the directional coupler and mode‐order converter based on the waveguide arrays show an ultrabroad bandwidth of 120 nm and are quite tolerant to significant structural deviations (−50–150 nm). As compared to the robust optical coupling in other topological waveguide arrays reported in recent works, the approach is more advantageous in terms of robustness against the variations in both waveguide width and gap distance, which is greatly favored in large‐scale photonic integration. This work could serve as a design principle for a new class of broadband and fabrication tolerant coupled‐waveguide devices, which can find applications in many fields including optical simulations of condensed matter physics, on‐chip optical communications, and quantum information processing. Abstract : The Thouless pumping process, an important example of topology in physics, is exploited to realize robust power coupling and mode‐order conversion in coupled‐waveguide devices. The topological designs show a broad bandwidth of 120 nm and a large fabrication tolerance of −50–150 nm to the structural deviations in waveguide width and gap distance.